Characterization of the Mechanical Properties of Fiberglass/Epoxy Prepreg Composites as Horizontal Axis Wind Turbine Blade Material: Influence of Fiber Orientation on Impact and Bending Strength - Istana, Budi; Alfredo, Fitto; Sunaryo, Sunaryo (Jurnal Polimesin, 2024)
This study aims to investigate the effect of fiber orientation on the impact and bending strength of fiberglass/epoxy prepreg composites used in horizontal axis wind turbine applications. The use of fiberglass/epoxy composites in the renewable energy industry, particularly in horizontal axis wind turbines, is increasing due to their superior mechanical properties. One crucial factor influencing the performance of these composites is the fiber orientation within the material structure. Proper fiber orientation can enhance impact and bending strength, which are critical for resisting dynamic and static loads during wind turbine operation. In this study, various fiber orientation angles were tested to determine their impact on composite performance. The analysis provides valuable insights for optimizing the design and improving the performance of wind turbines by maximizing the properties of the composite materials used. The study focused on 45° and 90° fiber orientations with epoxy resin as the matrix. The impact test results indicated that the highest impact strength was achieved with the 45° fiber orientation, showing a value of 0.113 J/mm² and an absorbed impact energy of 11.307 Joules. Similarly, the bending test results demonstrated that the 45° fiber orientation produced the highest bending strength. These findings highlight the significant effect of 45° fiber orientation on the impact strength and bending properties of the composite material. The results are expected to contribute to the development of more optimized composite materials for renewable energy applications, especially in the wind turbine industry.